MENAKAR PENEGAKAN HUKUM PRAKTIK POLITIK UANG (MONEY POLITIC) DALAM MEWUJUDKAN KEADILAN PEMILU (ELECTORAL JUSTICE) - Kurnia, Kamal fahmi (Faculty of Law, Universitas Pasundan, 2024)
The mechanism for enforcing money politics law has 2 (two) different legal dimensions, namely the election criminal dimension and the election administration dimension. Such conditions give rise to legal uncertainty in the process of enforcing the money politics that occurs. The principle of electoral justice is an important perspective in the process of enforcing money politics laws. This research aims to construct Money politics Law Enforcement that can Achieve Electoral Justice in Indonesia. This research uses a normative juridical approach, with secondary data as the main data. The data collection method was carried out by literature study of secondary data. Next, data analysis was carried out using qualitative descriptive methods. The conclusion of this research states that the construction of law enforcement of money political practices in the implementation of elections in Indonesia can be carried out by constructing 2 (two) aspects, namely certainty regarding types of money politics violations as a special type of criminal violation for elections and constructing law enforcement of money political practices through the establishment of judicial institutions. especially elections.